The COVID-19 pandemic and pulmonary arterial hypertension in Italy: adaptation, outcomes and valuable lessons learned. Issue 4 (6th October 2022) - Mickael, Claudia; Lee, Michael H.; Graham, Brian B.
The ongoing coronavirus disease 2019 (COVID-19) pandemic caused by widespread infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused immense morbidity and mortality worldwide. While COVID-19 has affected many patients with chronic comorbidities, its potential impact on patients with chronic diseases is of great concern, and particularly those with pulmonary arterial hypertension (PAH), as the viral infection also causes pulmonary vascular pathology [1]. PAH patients are prone to decompensated right heart failure resulting in hospitalisations and even deaths [2], with infections representing a common triggering factor [3]. Furthermore, even patients without underlying PAH can secondarily develop pulmonary hypertension due to acute respiratory distress syndrome (ARDS) [4], and COVID-19-associated ARDS also appears to cause pulmonary hypertension [5–7], which can be long-lasting [8–10]. This editorial summarises the key findings of R. Badagliacca and co-workers regarding the changes in care and clinical outcomes of PAH patients during the initial COVID-19 pandemic in Italy https://bit.ly/3ytgIjk